Relationship between previous hand hygiene training and hand hygiene behavior among elderly in Kudat - Mazlinda Musa; Hamidah Hassan; Rohani Mamat; Siti Fatimah Sa’at; Malehah Mohd Noh; Azizan Omar; Syed Syarizman Abd Rahim; Mohd Yusof Ibrahim; Nornazirah Azizan; Azali Saudi (Universiti Putra Malaysia, 2025)
In 2020, Malaysia achieved a significant milestone in its demographic transition by transitioning into an aged society. It was found that 6 out of every 10 COVID-19 deaths consisted of senior citizens aged 60 and above with chronic diseases. Hand hygiene is the cheapest yet the most ignored preventive measure in infection control. Thus, the aim of this study is to assess the relationship between previous hand hygiene training and hand hygiene behavior among older adult in Kudat. Materials and Methods: Simple Random sampling was used to the selected areas from the village head. Using Sample size calculator, 386 is the required sample size. Hand Hygiene Behavior questionnaire adapted from G.Aryan et al, 2021 study was used. Result: Analyses using Generalized LinerLinear model version SPSS 26. The dependent variable is Hand Hygiene Behavior score which has been classified into 3 groups, low, moderate and high. The intercept (independent variable) is previous training on Hand Hygiene, was found to be 2.073 (SE = .0237, 95% CI [2.026, 2.119], Wald χ2 = 7617.504, df = 1, p < .001), indicating that the expected value of Total Hand Hygiene is 2.073 when all predictors are equal to zero. We can conclude that both the intercept and Scale are statistically significant predictors of Hand Hygiene behavior. Conclusion: The hand hygiene training has positive impact on hand hygiene behavior among the rural older adult therefore it should be be conducted in regular interval.